Galactooligosaccharide (GOS) Fortified Formula Feeding in Premature Infants - Martono Tri Utomo; Muhammad Reza; Risa Etika; Talitha Y. Aden; Iwan S. Handoko; Ruth A. Alexander (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Nutritional problems are one of the serious problems in low birth weight or preterm infants. This causes medical and nutrition management of premature infants to be more individual. Objective: To evaluate the outcome of the premature infants with Galactooligosaccharides (GOS) fortified formula feedingMethods: This was prospective, open label cohort study that conducted during March- December 2019 in Neonatology Unit at the one of the main referral hospitals in East Java, Indonesia. The population of the study was very low birth weight infants (1,000 g - ≤1,500g) who needed formula feeding. Weight, body length, head circumference, fecal models and the incidence of diarrhea, colic, regurgitation, and vomiting was observed. Patients were observed for 28 days or adjusted according to length of stay.Results: Totally, 20 infants were included. Mean birth weight was 1236.2±148.5 grams. Mean total volume Galactooligosaccharides fortified formula at the start of recruitment was 209.4±46.1 ml and at the end of observation was 267.9±41.2 ml. There were change in amount and consistency of feces before and after intervention. No patient experienced adverse events (diarrhea, colic, regurgitation or vomiting) while consuming Galactooligosaccharides fortified formula. Conclusion: Galactooligosaccharides fortified formula in premature infant formula did not have a detrimental effect on premature infants and did not cause intolerance